2020
DOI: 10.1200/jco.20.00131
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus 1-Year Fixed-Duration Nivolumab in Previously Treated Advanced Non–Small-Cell Lung Cancer: CheckMate 153

Abstract: PURPOSE Limited data exist on the optimal duration of immunotherapy, including for non–small-cell lung cancer (NSCLC). We present an exploratory analysis of CheckMate 153, a largely community-based phase IIIb/IV study, to evaluate the impact of 1-year fixed-duration versus continuous therapy on the efficacy and safety of nivolumab. METHODS Patients with previously treated advanced NSCLC received nivolumab monotherapy (3 mg/kg every 2 weeks). Those still receiving treatment at 1 year, including patients perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 16 publications
0
97
1
1
Order By: Relevance
“…Although a prospective study indicated that treatment discontinuation was associated with detrimental survival in NSCLC, 3 CMR by FDG-PET selects a patient population with favorable response to treatment. In the presented cohort of patients, 15 of 27 (56%) patients with CMR have paused immunotherapy following FDG-PET, none of them has progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a prospective study indicated that treatment discontinuation was associated with detrimental survival in NSCLC, 3 CMR by FDG-PET selects a patient population with favorable response to treatment. In the presented cohort of patients, 15 of 27 (56%) patients with CMR have paused immunotherapy following FDG-PET, none of them has progressed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently published results from CheckMate-153 demonstrated inferior survival rates in patients ceasing immunotherapy after 1 year, 3 therefore, optimal treatment duration of immunotherapy in advanced NSCLC remains unknown. Protocols from published phase-III trials implemented treatment for a period of approximately 24 months or until evidence of disease progression or unbearable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…16 In the intent-totreat population, continuous nivolumab was associated with longer median OS compared with 1-year fixedduration treatment (not reached vs 28.8 months; HR, 0.62 (95% CI, 0.42 to 0.92)). 16 We conducted a multivariable analysis of baseline demographics and clinical variables to evaluate their association with progression. The results indicate that younger age, history of brain metastasis, and a higher post-PD-1 LDH were associated with earlier time to progression.…”
Section: Discussionmentioning
confidence: 88%
“… 15 In a recent exploratory analysis of CheckMate 153, which evaluated continuous versus 1-year fixed-duration nivolumab in previously treated advanced non-small cell lung cancer patients, continuing nivolumab beyond 1 year appeared to be associated with improved outcomes. 16 In the intent-to-treat population, continuous nivolumab was associated with longer median OS compared with 1-year fixed-duration treatment (not reached vs 28.8 months; HR, 0.62 (95% CI, 0.42 to 0.92)). 16 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation